Peran Pengasuhan Orang Tua Dalam Perkembangan Mental Emosional Anak Usia Pra Sekolah - Indriati, Ratna; Kristi, Yemima Icha Widya (KOSALA : Jurnal Ilmu Kesehatan, 2019)
Background: Optimal mental emotional development of early childhood will be very beneficial for the formation of children's personality in the future. The prevalence of people who experience a national mental emotional disorder is 6.0% (Riskesdas, 2013). Detection of mental emotional development in pre-school children is very important to do in early detection of mental emotional deviations / problems in children so that intervention can be done immediately. Child's mental emotional development is strongly influenced by the family environment. The success of character formation in children is influenced by parenting style. Purpose to determine the role of parenting in mental emotional development in preschool children. The benefits of research are to provide an overview of the importance of parenting right as an effort to support mental emotional development in children. The subject of study is 35 pre-school children at TK B Widya Wacana 4 Kartasura. Research in the form of analytic observation, correlation design with cross sectional method. Sampling in total sampling. The data obtained were analyzed by the Spearman Rank test with p = 0.05. The Result of Research is shows children with authoritative parenting 31 children (88.6%), permissive 4 children (11.4%). Children with normal mental emotional development 24 children (68.6%), there may be a problem with 11 children (31.4%). The results of the analysis of the role of parenting in the development of children's mental emotional use Rank Spearman test obtained p = 0.048 (p <0.05). The conclusion is parenting patterns play a role in the child's mental emotional development. Keywords: Mental emotional development of children, parenting parents